(untitled) (INNOVATIVE ECONOMY, 2020)
Matskiv V.V. WAYS TO IMPROVE THE FINANCIAL SUPPORT OF THE AGRICULTURAL SECTOR IN THE CONDITIONS OF ECONOMIC TRANSFORMATION Purpose. The aim of the article is the development of ways to improve the financial support of the agricultural sector in the conditions of economic transformation. Methodology of research. The study used a set of general and special research methods, in particular: historical and documentary analysis – to determine the conceptual basis of financial support of economic entities in the agricultural sector; graphical and tabular methods – to present the results of the analysis; methods of abstraction and generalization – to formulate conclusions and suggestions. Findings. The content of the financial support of the agricultural sector is generalized. The essence and the purpose of financial support are revealed. The expediency of developing a financial strategy for the development of the agricultural sector of Ukraine is substantiated and its components are identified. The main goals of investment policy in the agricultural sector to create optimal conditions for effective use of investment potential are established. The mechanism of the state support of agricultural commodity producers which has to combine various forms of maintenance is offered: direct (subsidy); indirect (preferential taxation); indirect (not directly related to agricultural production). Originality. A set of proposals for increasing the amount of funding for the agricultural sector of Ukraine for the use of strategic development reserves has been developed. The typology of financing schemes in accordance with the goals of economic entities in the agricultural sector is substantiated. The strategy of development of financial maintenance of agrarian sphere is offered. Practical value. The results of the study can be used by agricultural enterprises in the formation of effective policies for financing development activities in a changing competitive environment. Key words: financing, financial provision, financial resources, economic entities, agricultural enterprises, development strategy, agricultural sphere.